TINJAUAN YURIDIS PELAKSANAAN MAGANG CALON NOTARIS BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2014 (DI KOTA SAMARINDA) - Citra Wahyuni Ayu Pallawa (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThis research  review  on the implementation  of the apprentice Candidate Notary based on Act No. 2, 2014, in the city of Samarinda, this research using methods of Juridical Normative Juridical and Sociological, in this case the notary is a public official or officials who perform the duties of the state in legal services to the community in order to achieve legal certainty, A notary public is a powerful document maker in legal proocedings because  the deed-a deed which he has the power of proof is perfect and the certificate used by the parties as a means of proof.Notary  public in carrying out its duties related to the ethical values of the profession which regulated either in legislation or in the code of ethics of the profession of notary public itself, therefore the notary  should always be based on the provisions.One of  the conditions of the appointment of a notary public is an intern for 24 consecutive months the office of notary public, for internships is very necessary for a candidate notary to apply knowledge that has been gained  by the practice of a notary public lecture significantly, but in the process of apprenticeship apprentice Notary candidates don’t have the guidelines in carrying out the practice of science internships so that they get maximum not.